2018
DOI: 10.1515/ijamh-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melissa officinalis capsule on the mental health of female adolescents with premenstrual syndrome: a clinical trial study

Abstract: Introduction In spite of its importance, the psychological health requirements of adolescents are ignored; due to the occurrence of mental disorders in this age group and also public interest in the use of supplementary and alternative treatments such as herbal drugs for mental disorders, this study was carried out aimed at examining the impact of the Melissa officinalis capsule on the psychological health of female adolescents. Methodology In this randomized clinical trial study, 100 female adolescents were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
1
21
0
3
Order By: Relevance
“…Over the past decade, the use of complementary and alternative drugs has been increased to treat the problems of various groups of society, especially women, such as menopause, premenstrual syndrome, and sexual illness. [151617181920] The familiarity of the medical team and the research team has become even more prominent in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the use of complementary and alternative drugs has been increased to treat the problems of various groups of society, especially women, such as menopause, premenstrual syndrome, and sexual illness. [151617181920] The familiarity of the medical team and the research team has become even more prominent in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, MO contains different classes of phytochemicals such as essential oils, terpenoids and polyphenolic compounds such as flavonoids, rosmarinic acid (RA) and tannins (Dastmalchi et al., 2008; De Sousa et al., 2004). In traditional medicine, MO has been extensively used for treatment of many psychological disorders such as nervous sleeping disorders, stress, anxiety and depression (Awad, Muhammad, Durst, Trudeau, & Arnason, 2009; Heydari, Dehghani, Emamghoreishi, & Akbarzadeh, 2018; Ibarra, Feuillere, Roller, Lesburgere, & Beracochea, 2010; Khodaei et al., 2017; Lin et al., 2015). It has anti‐inflammatory, anti‐microbial, anti‐oxidative, sedative and neuroprotective actions (López et al., 2009; Miraj, Rafieian, & Kiani, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, previous studies into of the effects of aromatherapy on the social functions of PMS have been limited, with some articles having reported that Melissa officinalis in capsule form was associated with reduced severity of physical, mental and social symptoms . It should be noted that ameliorating physical and mental symptoms of PMS could be expected to improve social functions.…”
Section: Discussionmentioning
confidence: 99%